E3 Ligase Ligands in Successful PROTACs: An Overview of Syntheses and Linker Attachment Points - Bricelj, Aleša; Steinebach, Christian; Kuchta, Robert; Gütschow, Michael; Sosič, Izidor (Frontiers in Chemistry, 2021)
Proteolysis-targeting chimeras (PROTACs) have received tremendous attention as a new and exciting class of therapeutic agents that promise to significantly impact drug discovery. These bifunctional molecules consist of a target binding unit, a linker, and an E3 ligase binding moiety. The chemically-induced formation of ternary complexes leads to ubiquitination and proteasomal degradation of target proteins. Among the plethora of E3 ligases, only a few have been utilized for the novel PROTAC technology. However, extensive knowledge on the preparation of E3 ligands and their utilization for PROTACs has already been acquired. This review provides an in-depth analysis of synthetic entries to functionalized ligands for the most relevant E3 ligase ligands, i.e. CRBN, VHL, IAP, and MDM2. Less commonly used E3 ligase and their ligands are also presented. We compare different preparative routes to E3 ligands with respect to feasibility and productivity. A particular focus was set on the chemistry of the linker attachment by discussing the synthetic opportunities to connect the E3 ligand at an appropriate exit vector with a linker to assemble the final PROTAC. This comprehensive review includes many facets involved in the synthesis of such complex molecules and is expected to serve as a compendium to support future synthetic attempts towards PROTACs.